LaRa after RISE: Expected improvement in the Mars rotation and interior models. (January 2020) - Péters, M.-J.; Le Maistre, S.; Yseboodt, M.; Marty, J.-C.; Rivoldini, A.; Van Hoolst, T.; Dehant, V.
Abstract: Two years after InSight's arrival at Mars, the ExoMars 2020 mission will land on the opposite side of the red planet. Similarly to InSight, which carries the RISE (Rotation and Interior Structure Experiment) radio-science experiment, the ExoMars mission will have on board the Lander Radio-science (LaRa) experiment. The X-band transponders on RISE and LaRa, allowing for direct radio-link between the landers and stations on Earth, are dedicated to the investigation of Mars' deep interior through the precise measurement of the planet's rotation and orientation. The benefit of having LaRa after RISE for the determination of the Mars orientation and rotation parameters is demonstrated and the resulting improved constraints on the interior structure of Mars and, in particular, on its core are quantified via numerical simulations. In particular, we show that the amplitudes of the semi-annual prograde ( p 2 ) and the ter-annual retrograde ( r 3 ) nutations will be determined with a precision of 6 and 4 milliarcseconds respectively by combining 700 days of RISE data with 700 days of LaRa data, about 35% more precise than what is expected from RISE alone. The impact of such an improvement on the determination of the core size of Mars is discussed and shown to be significant. Highlights: Mars rotation and Orientation Parameters (MOP) determination using Doppler data from landers. Assessment of the benefit of having LaRa after RISE for the MOP determination. Implications of the RISE and LaRa combination on our knowledge of the interior of Mars. An independent validation of the RISE results provided by LaRa.